AN ANALYSIS OF THE NATIONAL SECURITY LAW IN SPAIN AS A COMPREHENSIVE SECURITY LAW. PROPOSAL TO INCLUDE SECURITY ON LAND ROUTES AS AN AREA OF SPECIAL INTEREST FOR NATIONAL SECURITY (Journal of the Spanish Institute for Strategic Studies, 2018)
A National Security Law has officially come into force in Spain,establishing a National Security System and contributing to internationalsecurity. Its key components are National Defence, Public Security andExternal Action. With a view to improving the necessary anticipation,prevention, analysis of, reaction and resistance to, as well as the recoveryfrom risks and threats that might compromise National Security,the proposal is presented here for a new cross-cutting dimension notspecifically contemplated heretofore, which is the Security of LandRoutes and the Security of Mobility and Land Transport, and for Spainto assume a leading role in the EU Commissariat for Security Union.